Physical performance measurement in chronic low back pain: measuring physical capacity or pain-related behaviour?. (September 2013) - Huijnen, Ivan P. J.; Verbunt, Jeanine A.; Wittink, Harriet M.; Smeets, Rob J. E. M.
Abstract: In patients with chronic low back pain (CLBP), a patient's level of physical functioning is evaluated to determine the impact of pain on physical functioning. It appears that in various performance tests the influence of non-physiological factors differs. It is unclear which performance tests are best suited for measurement of maximum capacity or pain-related behaviour. The main aim of the present review is to highlight the influence of psychological factors during different types of performance testing in patients with CLBP. The degree in which pain-related and psychological factors influence test outcome differs between performance tests. A minimum influence of pain intensity and psychological factors is found in (sub)maximal exercise testing in patients who are able to complete the test. The influence of pain intensity and psychological factors is most prominent in holding endurance tasks evaluating the duration a patient can hold a certain weight. In order to decide which assessment tool for physical performance can best be used for the evaluation of physical functioning in patients with CLBP, one should specifically consider the question that has to be answered. In case a patients' physical capacity has to be objectified, another assessment tool seems preferred compared with a situation in which a patient's pain-related behaviour is aimed to be assessed.